(untitled) (Salam International Academic Journal, 2019)
This particular discussion & research is based on a few indispensable subjects which includes understanding of imprisonment, validity, historical background & process; effects of imprisonment under the Islamic law & Sharia, which enlighten the mentality & comprehension of students. At the beginning, we have to know the literal and figurative meaning of imprisonment; definitions of imprisonment in accordance to law that reveals how to put restriction (to imprison) on someone’s natural liberty for selected term at a specific place. The history of confinement is pretty long, which begins the same time as the history of mankind starts; in various civilizations imprisonment carried different forms and types, but this session of the discussion is mainly based on the type of impressment & accountability of prisoners and behavior towards the prisoners before the revolution of Islam in the term of ignorance. Imprisonment is considered to be the requirement of time, and it had various forms in Islamic law and Sharia, but Prophet Muhammad peace be upon him always strongly advised his companions to behave properly and show kindness to prisoners. The recommended laws and regulations of Prophet Muhammad peace be upon him were implemented by his mates with some high standards, which remained an example for the entire mankind. Prophet Muhammad peace be upon him always showed hospitable behavior towards prisoners who were caught during the war and providing them the food, which they could not access and they were deprived from those foods. In research there is discussion about the confinement based on the sharia law and Fiqa. Both discuss the legal punishment which is used as tools to achieve the selected targets and goals. In general, we can say that the fundamental objective of imprisonment is to redress the person again which is mentioned in the research as well. During the prison term the prisoners have to rethink about all their done activities and meanwhile the accountable administrations and authorities have to place on ground some effective training and reforming methods in order to present a sound personality to society, not only this the person should stop vandalism, corruption and encroachment. The prisoners after receiving training must spite all illegal actions and deeds. On the other hand, they should sense the responsibility of serving society, work for the development of the society and imagine the relief of the society. Research also discusses the negative effects of imprisonment; sometime the accountable authorities neglect their role of redressing and training the prisoners due to their sluggishness. Most of the times the lock ups are converted to a crime scene due to the lack of attention of the authorities which eventually shows negative health and economical effects on prisoners, their families, offspring, and wives. Finally, there were some important recommendations to the concerned authorities and asked them to change the form of imprisonment based on quality and quantity.